Correlation between cell-mediated immunity and clinical forms of paracoccidioidomycosis - Mota, N. G S [UNESP]; Rezkallah-Iwasso, M. T. [UNESP]; Peraçoli, Maria Terezinha Serrão [UNESP]; Audi, R. C. [UNESP]; Mendes, Rinaldo Poncio [UNESP]; Marcondes, J. [UNESP]; Marques, Silvio Alencar [UNESP]; Dillon, N. L. [UNESP]; Franco, M. F. [UNESP] (Oxford University Press (OUP), 1985)
Cellular immune response to specific and non-specific stimulants was investigated, both in vivo and in vitro, in 29 healthy controls and in 53 previously untreated patients with the chronic isolated organic form (CIOF), the chronic mixed form (CMF) and the acute progressive form (APF) of paracoccidioidomycosis. The study included skin tests to Paracoccidioides brasiliensis antigen (PbAg) and phytohaemagglutinin (PHA), DNCB sensitization, determination of T lymphocytes and complement rosette-forming cells, lymphocyte transformation and leucocyte migration inhibition tests using PbAg and PHA. Patients displayed staggered cutaneous response to PHA and to PbAg, with marked decrease in intensity in the APF group. DNCB sensitization test and proliferative response of lymphocytes to PHA and PbAg were severely depressed in most of the patients. Leucocyte migration inhibition indices to PbAg were highly positive, while response to PHA was slightly decreased regardless of the clinical form. The number of T lymphocytes was reduced in most of patients and in them the number of complement-rosette forming cells was normal. The distribution of patients according to a suppression index, based in the results of the tests employed, revealed a tendency towards an increased degree of cellular immunosuppression from the least severe (CIOF) to the most severe (APF) clinical form of the disease. On the whole, the present study demonstrated a gamut of immunological reactivity in paracoccidioidomycosis. © 1985.
Keywords: fungus antigen; phytohemagglutinin; adolescent; adult; aged; cellular immunity; female; human; immunology; leukocyte; leukocyte count; leukocyte migration inhibition test; lymphocyte activation; male; Paracoccidioides; rosette formation; skin test; South American blastomycosis; Adolescent; Adult; Aged; Antigens, Fungal; Cell Migration Inhibition; Female; Human; Immunity, Cellular; Leukocyte Count; Leukocytes; Lymphocyte Activation; Male; Middle Age; Paracoccidioidomycosis; Phytohemagglutinins; Rosette Formation; Skin Tests; Support, Non-U.S. Gov't